Steady-state VO2 above mlss: evidence that critical speed better represents maximal metabolic steady state in well-trained runners - Nixon, R. J.; Kranen, S. H.; Vanhatalo, A.; Jones, A. M. (European Journal of Applied Physiology, 2021)
The metabolic boundary separating the heavy-intensity and severe-intensity exercise domains is of scientific and practical interest but there is controversy concerning whether the maximal lactate steady state (MLSS) or critical power (synonymous with critical speed, CS) better represents this boundary. We measured the running speeds at MLSS and CS and investigated their ability to discriminate speeds at which VO2 was stable over time from speeds at which a steady-state VO2 could not be established. Ten well-trained male distance runners completed 9-12 constant-speed treadmill tests, including 3-5 runs of up to 30-min duration for the assessment of MLSS and at least 4 runs performed to the limit of tolerance for assessment of CS. The running speeds at CS and MLSS were significantly different (16.4 ± 1.3 vs. 15.2 ± 0.9 km/h, respectively; P < 0.001). Blood lactate concentration was higher and increased with time at a speed 0.5 km/h higher than MLSS compared to MLSS (P < 0.01); however, pulmonary VO2 did not change significantly between 10 and 30 min at either MLSS or MLSS + 0.5 km/h. In contrast, VO2 increased significantly over time and reached VO2max at end-exercise at a speed ~ 0.4 km/h above CS (P < 0.05) but remained stable at a speed ~ 0.5 km/h below CS. The stability of VO2 at a speed exceeding MLSS suggests that MLSS underestimates the maximal metabolic steady state. These results indicate that CS more closely represents the maximal metabolic steady state when the latter is appropriately defined according to the ability to stabilise pulmonary VO2.